2017
DOI: 10.1371/journal.pone.0184965
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde pyelography predicts retrograde ureteral stenting failure and reduces unnecessary stenting trials in patients with advanced non-urological malignant ureteral obstruction

Abstract: ObjectiveTo evaluate predictive factors for retrograde ureteral stent failure in patients with non-urological malignant ureteral obstruction.Materials and methodsBetween 2005 and 2014, medical records of 284 malignant ureteral obstruction patients with 712 retrograde ureteral stent trials including 63 (22.2%) having bilateral malignant ureteral obstruction were retrospectively reviewed. Retrograde ureteral stent failure was defined as the inability to place ureteral stents by cystoscopy, recurrent stent obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Seven studies reported on failure of endoscopic urinary diversion [3,8–14]. We found a failure rate of 32% (95% CI 21–45%; I 2 = 88%; Fig.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Seven studies reported on failure of endoscopic urinary diversion [3,8–14]. We found a failure rate of 32% (95% CI 21–45%; I 2 = 88%; Fig.…”
Section: Resultsmentioning
confidence: 71%
“…We found a total of 970 articles with the search strategies. Finally, nine studies met the inclusion criteria [3,[8][9][10][11][12][13][14][15] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 468 were excluded by title and abstract screening, and a further 189 were excluded after full‐text assessment. Of the studies screened, 82 met the study criteria and were included in this review 4–85 . Figure 1 illustrates the process.…”
Section: Resultsmentioning
confidence: 99%
“…The success rates of retrograde ureteral stents have improved steadily along the years, even so, the failure rates have been reported to be as high as 40% with the traditional single polymeric ureteral stents [15]. In addition to progression of the primary tumour, stent occlusion due to urine viscosity in combination with the aggregation of fragments and macromolecules is a frequent cause of stent failure [16,17], as are external compressive forces, mucous production, and urothelial sloughing.…”
Section: Discussionmentioning
confidence: 99%